Low-Frequency Magnetic Sensing Using Magnetically Modulated Microcavity Resonant Mode - Xinrong Yang; Jiamin Rong; Enbo Xing; Jianglong Li; Yujie Zhang; Yanru Zhou; Wenyao Liu; Huanfei Wen; Jun Tang; Jun Liu (Micromachines)
We propose a low-frequency magnetic sensing method using a magnetically modulated microcavity resonant mode. Our magnetically sensitive unit with periodically changing magnetic poles is formed by combining an AC excitation coil with a microcavity. The microcavity vibrates at the frequency of the AC amplitude-modulated signal and changes its resonant mode when the sensing unit interacts with a low-frequency magnetic field. Signal processing is performed on the resonant spectrum to obtain low-frequency magnetic signals. The results of the experiment show that the measured sensitivity to a 0.5 Hz magnetic field is 12.49 V/mT, and a bias instability noise of 16.71 nT is achieved. We have extended the measurable frequency range of the whispering gallery mode microcavity magnetometer and presented a development in microcavity magnetic sensing and optical readout.